Peripheral Neuropathies of Rheumatologic Disease and Gluten-Related Disorders - Reda, Haatem; Chin, Russell L. (Seminars in Neurology, 2014)
Peripheral nervous system disease is a common and often debilitating feature of many systemic rheumatologic disorders. Such involvement takes many forms, reflecting the variety of underlying pathophysiology, though most patients present with painful multifocal neuropathy (usually vasculitic) or a distal sensory more than motor peripheral neuropathy (sometimes vasculitic and nearly always axonal). The presence of peripheral nervous system involvement is often an early signal of the generalization of inflammatory disease in blood vessels or extravascular tissues, though peripheral neuropathy is not itself an independent predictor of mortality. Nonetheless, progressive multifocal neuropathy, motor neuropathy, small fiber neuropathy, and sensory neuronopathy should be treated early and aggressively with immunosuppression (or the gluten-free diet in appropriate situations) to limit morbidity. Given the rapidly evolving therapeutic landscape, partnership with a rheumatologist is essential. Treatment is usually sustained for 1 to 2 years, and remission is possible in many cases within 6 to 12 months, with variable rates of relapse and treatment resistance. Patients should be meticulously monitored for relapse with serial laboratory testing, electrodiagnostic studies, and clinical examination. Functional rating scores, such as the neuropathy impairment scale and the total neuropathy score are useful for longitudinal assessment.
Keywords: vasculitis; rheumatologic; neuropathy; celiac; fibromyalgia